Unlocking Reading Comprehension: A Comparative Study of Individual vs. Group Annotation Strategies - Katemba, Caroline Victorine (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study investigates the effectiveness of individual versus group annotation procedures in improving reading comprehension among students learning English as a foreign language. The study's goal is to examine the effects of two annotation procedures, individual and group annotations, on students' reading comprehension and analyze their reactions to these strategies. Data were obtained from two groups of eighth-grade students at SMPN 5 Lembang, one using individual annotation and the other employing group annotation methodologies. The study used pre- and post-tests to assess comprehension improvement, as well as statistical analyses (SPSS) to compare the two groups. The results showed that, while both strategies improved reading comprehension, students who used group annotation made larger gains. The group annotation approach also increased students' interest and motivation, as shown by more favorable responses to the strategy in post-treatment questionnaires. The findings indicate that group annotation is more effective than individual annotation in improving reading comprehension because it promotes better teamwork, motivation, and a deeper grasp of the material. Furthermore, the study emphasizes the need to tailor reading tactics to individual characteristics among students, implying that group annotation can be a more interesting and successful approach to developing reading abilities.